Analisis Pengaruh Bahan Bakar Alternatif pada Lemari Pengasap Ikan terhadap Kualitas Produk Hasil Asapan - Nugroho, Setyawan Dwi; Soeparman, Sudjito; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
This study was conducted to determine the effect of the amount of fuel in the combustion chamber on the fish smoking kiln to temperature and temperature distribution in the smoke room as well as the quality of the smoked fish.This study used 3 types of fuel those are dry coconut shell, coconut fiber and sugarcane pulp briquette. Temperature needed in the smoke room for 3 hours is 80° C, andthe fish smoked ismilkfish. The result showed that to achieve the same smoking temperature, it required the amount of dry coconut shell as much as 1045 grams, while the coconut fiber as much as 1730 grams and sugarcane pulp briquette as much as 2055 grams. The temperature of each fishing point is relatively even with a maximum temperature difference of 1.38%, while the difference between the setting temperature and the temperature at the maximum fish points is 8.88%. It can be concluded that the heat value, particle density rate and combustion rate (heat release) of fuel affect the amount and distribution of fuel to the temperature change in the fish smoking room in the fish smoking kiln. The quality of smoked fish products with 3 types of fuels meets SNI 2725.1.2009.